Completeness of HIV reporting on death certificates for Floridians reported with HIV infection, 2000–2011. Issue 1 (2nd January 2016) - Trepka, Mary Jo; Sheehan, Diana M.; Fennie, Kristopher P.; Niyonsenga, Theophile; Lieb, Spencer; Maddox, Lorene M.
Abstract : Human immunodeficiency virus (HIV) mortality is used as a key measure to monitor the impact of HIV throughout the world. It is important that HIV be correctly recorded on death certificates so that the burden of HIV mortality can be tracked accurately. The objective of this study was to determine the extent of failure to correctly report HIV on death certificates and examine patterns of incompleteness by demographic factors. Causes of death on death certificates of people infected with HIV reported to the Florida HIV surveillance system 2000–2011 were analyzed to determine the proportion without mention of HIV who had an underlying cause of death suggestive of HIV based on World Health Organization recommendations. Of the 11, 989 deaths, 8089 (67.5%) had an HIV code (B20–B24, R75) as any of the causes of death, 3091 (25.8%) had no mention of HIV and the underlying cause was not suggestive of HIV, and 809 (6.7%) had no mention of HIV but the underlying cause was suggestive of HIV. Therefore, 9.1% (809/8898) of probable HIV-related deaths had no mention of HIV on the death certificate. Dying within 1 month of HIV diagnosis was the factor most strongly associated with no mention of HIV when the underlying cause was suggestive of HIV on the death certificate. The results suggest that HIV mortality using only vital records may underestimate actual HIV mortality by approximately 9%. Efforts to reduce incompleteness of reporting of HIV on death certificates could improve HIV-related mortality estimates.